A cluster randomized controlled trial of extending ART refill intervals to six-monthly for anti-retroviral adherence clubs - Wilkinson, L; Grimsrud, A; Cassidy, T; Orrell, C; Voget, J; Hayes, H; Keene, C; Steele, SJ; Gerstenhaber, R (BioMed Central, 2019)
Background: The antiretroviral therapy (ART) adherence club (AC) differentiated service delivery model, where clinically stable ART patients receive their ART refills and psychosocial support in groups has supported clinically stable patients’ retention and viral suppression. Patients and health systems could benefit further by reducing visit frequency and increasing ART refills. We designed a cluster-randomized control trial comparing standard of care (SoC) ACs and six-month ART refill (Intervention) ACs in a large primary care facility in Khayelitsha, South Africa.